Healthcare-Associated Infections in Pediatric and Neonatal Intensive Care Units: Impact of Underlying Risk Factors and Antimicrobial Resistance on 30-Day Case-Fatality in Italy and Brazil. (11th August 2016) - Folgori, Laura; Bernaschi, Paola; Piga, Simone; Carletti, Michaela; Cunha, Filippe Pirrone; Lara, Paulo Henrique Rodriguez; de Castro Peixoto, Nicholas Cafieiro; Alves Guimarães, Bárbara Gomes; Sharland, Mike; Araujo da Silva, André Ricardo; Ciofi degli Atti, Marta
Abstract : OBJECTIVES: To describe trends in the epidemiology of healthcare-associated Infections (HAIs) in pediatric/neonatal intensive care units (ICUs) and to evaluate risk factors and impact of multidrug resistance in children admitted to ICUs. DESIGN: Multicenter, retrospective, cohort study with a nested case-control study conducted from January 1, 2010, through December 31, 2014. SETTING: Three tertiary care pediatric hospitals in Italy and Brazil with a total of 103 ICU beds. PATIENTS: Inclusion criteria were admission to ICU during the study period, age at onset less than 18 years, and microbiologically confirmed HAI. RESULTS: A total of 538 HAIs in 454 children were included; 93.3% of patients had comorbidities. Bloodstream infections were the leading pattern (45.4%). The cumulative incidence of HAI was 3.6/100 ICU admissions and the crude 30-day fatality rate was 5.7/1, 000 admissions. The most frequently isolated pathogens were Enterobacteriaceae, followed by Pseudomonas aeruginosa and Staphylococcus aureus . Forty-four percent of isolates were multidrug-resistant (MDR). Two multivariate logistic regressions were performed. Factors independently associated with an MDR-HAI were country, previous antibiotics, transplantation, major surgery, and colonization by an MDR strain. Factors independently associated with 30-day case fatality were country, previous transplantation, fungal infection, bloodstream infection, lower respiratory tract infection, and infection caused by MDR strains. CONCLUSIONS: Infection control and prevention can limit the spread of MDR strains and improve outcomes. Targeted surveillance programs collecting neonatal and pediatric HAI/bloodstream infection data and outcomes would allow global benchmarking. The next step is to identify methods to monitor key HAIs and integrate these into affordable intervention programs. Infect Control Hosp Epidemiol 2016;1–8